El control interno y la gestión logística en la Municipalidad Provincial de Requena en el periodo 2022 - Medina Quina, Jose Luis Antonio (2024)
This research focuses on the evaluation of internal control and logistics management, which was developed through a quantitative and correlational approach and non-experimental design, including 95 people as the study population, with the main objective being to determine the relationship existing between Internal Control and Logistics Management in the Provincial Municipality of Requena, in the Loreto region, period 2022. The investigation has identified that internal control is at a good level in 60.53%, regular in 31.58% and finally bad in 7.89%. , there is adequate management of internal control in the provincial municipality of Requena, on the other hand, it was identified that logistics management is of a good level in 51.32%, Regular in 36.84%, and finally Bad in 11.84%, evidencing adequate management of the Logistics Management. Likewise, Spearman's Rho Correlation Coefficient was identified between Internal Control and Logistics Management equal to Rho=0.861 and value of Sig. (bilateral)=0.000, so it is concluded that there is a high positive relationship between Control Internal and Logistics Management in the Provincial Municipality of Requena, in the Loreto region, period 2022.